Repair of Adult Mammalian Heart After Damages by Oral Intake of Gu Ben Pei Yuan San - Cui, Baiping; Zheng, Yufan; Zhou, Xinyan; Zhu, Jiaqi; Zhuang, Jiexian; Liang, Qianqian; Xu, Chen; Sheng, Wei; Huang, Guoying; Luan, Lina; Sun, Ning (Frontiers in Physiology, 2019)
ABSTRACT Adult mammalian heart repair after myocardial damage is highly inefficient due to the post-mitotic nature of cardiomyocytes. Interestingly, in Traditional Chinese Medicine (TCM), there are reported effective treatments of myocardial infarction and heart failure in adult humans by oral intake of a TCM concoction named Gu Ben Pei Yuan San (GBPYS) which is composed of Panax ginseng, Velvet antler, Gekko gecko linnaeus tail, Human placenta, Trogopterus dung, Panax notoginseng, and Amber. We fed the mice with GBPYS after myocardial damages through everyday self-feeding. We then examined the effect of everyday oral intake of GBPYS on improving cardiac function and myocardial repair in adult mice after apical resection or myocardial infarction. We found that long-term oral intake of GBPYS significantly improved cardiac function after myocardial damages in adult mice. Brdu, Phospho-histone 3, and AuroraB staining indicated increased cell proliferation at the border zone of MI after TCM feeding. GBPYS feeding reduced organ inflammation and is nontoxic to mice after long-term oral intake. Further, serum derived from TCM fed MI rats promoted division of both neonatal rat cardiomyocytes and human iPSC-derived cardiomyocytes In vitro. Oral intake of GBPYS improved heart repair after myocardial damages in adult mice. Our results suggest that there are substances present in GBPYS that help improve adult mammalian heart repair after MI. Also, it could be a good choice of non-invasive alternative therapy for myocardial damages and heart failure after rigorous clinical study in the future.